1990
DOI: 10.1016/0014-5793(90)80164-e
|View full text |Cite
|
Sign up to set email alerts
|

The ribonuclease from an extinct bovid ruminant

Abstract: The sequence of the ribonuclease from the ancestor of swamp buffalo, river buffalo, and ox, corresponding approximately to Pachyporrux lutidem, an extinct ruminant known from the fossil record, has been reconstructed using the rule of 'maximum parsimony'. This protein and two sequences that may have been intermediates in the evolution of modern ribonuclease have been constructed in the laboratory by site-directed mutagenesis, and their properties examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
53
0
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 118 publications
(55 citation statements)
references
References 18 publications
0
53
0
1
Order By: Relevance
“…Since the first ancestral reconstructions by Malcolm et al (1990) and Stackhouse et al (1990), there have now been more than 40 published ASR studies and two common properties exhibited by inferred ancestral proteins/enzymes have emerged: (i) high stability-both thermostability (usually measured as the temperature midpoint of thermal denaturation, T m , or optimum temperature for activity, T opt ) and kinetic stability (measured as the free energy for unfolding, DG z NÀU )- (Akanuma et al 2013;Butzin et al 2013;Gaucher et al 2003Gaucher et al , 2008Groussin et al 2015;Hobbs et al 2012;Miyazaki et al 2001;Perez-Jimenez et al 2011;Risso et al 2013;Watanabe et al 2006a;Watanabe and Yamagishi 2006b) k cat and (ii) high catalytic activity and/or catalytic efficiency (usually expressed as k cat and k cat / K M , respectively) (Stackhouse et al 1990;Akanuma et al 2013;Butzin et al 2013;Groussin et al 2015;Hobbs et al 2012;Perez-Jimenez et al 2011;Risso et al 2013;Watanabe and Yamagishi 2006b;Jermann et al 1995). These increases in stability and catalytic activity compared with contemporary proteins/enzymes can be dramatic, for example Risso et al (2013) reported that their inferred ancestral b-lactamases were more stable than their contemporary descendants by as much as 35°C, and Perez-Jimenez et al (2011) found that their reconstructed ancestral thioredoxins displayed catalytic rate constants up to 30-fold higher than modern thioredoxins at pH 5, as well as being up to 32°C more stable.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first ancestral reconstructions by Malcolm et al (1990) and Stackhouse et al (1990), there have now been more than 40 published ASR studies and two common properties exhibited by inferred ancestral proteins/enzymes have emerged: (i) high stability-both thermostability (usually measured as the temperature midpoint of thermal denaturation, T m , or optimum temperature for activity, T opt ) and kinetic stability (measured as the free energy for unfolding, DG z NÀU )- (Akanuma et al 2013;Butzin et al 2013;Gaucher et al 2003Gaucher et al , 2008Groussin et al 2015;Hobbs et al 2012;Miyazaki et al 2001;Perez-Jimenez et al 2011;Risso et al 2013;Watanabe et al 2006a;Watanabe and Yamagishi 2006b) k cat and (ii) high catalytic activity and/or catalytic efficiency (usually expressed as k cat and k cat / K M , respectively) (Stackhouse et al 1990;Akanuma et al 2013;Butzin et al 2013;Groussin et al 2015;Hobbs et al 2012;Perez-Jimenez et al 2011;Risso et al 2013;Watanabe and Yamagishi 2006b;Jermann et al 1995). These increases in stability and catalytic activity compared with contemporary proteins/enzymes can be dramatic, for example Risso et al (2013) reported that their inferred ancestral b-lactamases were more stable than their contemporary descendants by as much as 35°C, and Perez-Jimenez et al (2011) found that their reconstructed ancestral thioredoxins displayed catalytic rate constants up to 30-fold higher than modern thioredoxins at pH 5, as well as being up to 32°C more stable.…”
Section: Introductionmentioning
confidence: 99%
“…If the sequence of an ancestral protein can be re-created, the protein can be synthesized and expressed, and its characteristics can be determined experimentally (Malcolm et al 1990;Stackhouse et al 1990;Shih et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…This implies that one must retrieve the ancient protein and determine its structure to evaluate a consensus structural model. While not impossible [40], this is certainly inconvenient. Nevertheless, this experience shows why a jury evaluating a consensus prediction must find and consider several experimental structures [39] before rendering a strong verdict, Weak verdicts can, of course, be rendered at any time.…”
Section: Some More Structures Emergementioning
confidence: 99%
“…A consensus model might be viewed as representing the structure of the most recent common ancestor of the protein family being examined [40]. In this view, the ancestor of the sequences in the multiple alignment used to make the SH3 prediction contained a helix that was retained in the PI3K SH3 domains (not included in this alignment) and lost in the other domains.…”
Section: Some More Structures Emergementioning
confidence: 99%